The state of anti-oxidation system in rats under chemically induced cancerogenesis and influence by complexly modulated ultra-low frequency magnetic field (ULF MF) - Kit, Oleg I.; Shikhlyarova, Alla I.; Frantsiyants, Elena M.; Cheryarina, Natalia D.; Tkalya, Lyudmila D. (Cardiometry, 2017)
At present, control of properties of biological membranes as targets of magnetic field applications within a living cell is the subject of considerable discussion in the scientific community. Experimental studies carried out by us demonstrate that ULF MF has an access to the most important mechanisms of tumor growth. The most likely mechanism among them is that responsible for the processes of free-radicals oxidation. Therefore, our research work was aimed at studies of influences of ULF MFon indicators of the anti-oxidation system in blood plasma and blood cells in rats in the chemically induced cancerogenesis. Our experimental studies were performed in 45 outbred albino male rats having a body mass from 160 to 180 g. The state of the anti-peroxidation protection of cell membranes was assessed by indicators of the fermentation subsystem of AOS (catalase, TPA, SOD), and the state of the non-fermentive subsystem of AOS was estimated by indicators of the concentrations of vitamins A and E in blood serum. A prolonged latency period in the chemically induced cancerogenesis, obtained in our experiments, is treated by us as a positive effect produced by the ULF MF therapy that was found to be in correlation with the maintenance or restoration of the level of the functional activity of the anti-oxidation system in blood of the rats. Moreover, we have detected that it is precisely these immune competent cells which are the main point of applications in responses by the anti-oxidation system to ULF MF exposure that confirms our assumptions that the cancerogenesis process can be controlled by ULF MF.